Heat stress incident prevalence and tennis matchplay performance at the Australian Open - Smith, M. T.; Reid, M.; Kovalchik, S.; Woods, T. O.; Duffield, R. (Journal of Science and Medicine in Sport, 2018)
Objectives: To examine the association of wet bulb globe temperature (WBGT) with the occurrence of heat-related incidents and changes in behavioural and matchplay characteristics in men`s Grand Slam tennis. Design: On-court calls for trainers, doctors, cooling devices and water, post-match medical consults and matchplay characteristic data were collected from 360 Australian Open matches (first 4 rounds 2014-2016). Methods: Data were referenced against estimated WBGT and categorised into standard zones. Generalised linear models assessed the association of WBGT zone on heat-related medical incidences and matchplay variables. Results: On-court calls for doctor (47% increase per zone, p = 0.001), heat-related events (41%, p = 0.019), cooling devices (53%, p < 0.001), and post-match heat-related consults (87%, p = 0.014) increased with each rise in estimated WBGT zone. In WBGT`s >32 °C and >28 °C, significant increases in heat-related calls (p = 0.019) and calls for cooling devices (p < 0.001), respectively, were evident. The number of winners (-2.5 ± 0.006% per zone, p < 0.001) and net approaches (-7.1 ± 0.008%, p < 0.001) reduced as the estimated WBGT zone increased, while return points won increased (1.75 ± 0.46, p < 0.001). When matches were adjusted for player quality of the opponent (Elo rating), the number of aces (5 ± 0.02%, p = 0.003) increased with estimated WBGT zone, whilst net approaches decreased (7.6 ± 0.013%, p < 0.001). Conclusions: Increased estimated WBGT increased total match doctor and trainer consults for heat related-incidents, post-match heat-related consults (>32 °C) and cooling device callouts (>28 °C). However, few matchplay characteristics were noticeably affected, with only reduced net approaches and increased aces evident in higher estimated WBGT environments.